Destructive Diagenesis Observed in Outcrop Examples of Neogene Sandstone Reservoir and Clay Contact Zones, Miri, Northern Sarawak - Franz L. Kessler; John Jong (Berita Sedimentologi, 2019)
The occurrence of diagenetic siderite and iron oxide deposits has been recognized in offshore subsurface reservoirs of Baram Delta fields. Iron-rich intra-reservoir deposits are relatively common in coastal Sarawak, but good examples are rare. In this article, we present outcrop examples of the Miri area. In three selected locations, geometries and composition of diagenetically-derived iron precipitates can be explored, measured and analyzed. The destructive impact of siderite rims on net reservoir volume for STOIIP calculation, and their potential interaction with chemicals used for enhanced oil recovery (EOR) is also noted.